Botulinum toxin in the treatment of gummy smile (Journal of Face Aesthetics, 2020)
A gummy smile is an excessive exposure of the gums while smiling. There are four types: anterior- excessive gum exposure from canine to canine, posterior — excessive gum exposure in the lateral segment, mixed — combining the anterior and posterior components, and asymmetrical — with a disproportion between the right and left side. The causes of gingival smile include: skeletal defect, delayed passive tooth eruption, nasal septal dysplasia, and excessive muscle activity. A simple, fast and minimally invasive method of gummy smile therapy caused by excessive muscle activity is the supply of botulinum toxin type A to the muscles responsible for a given type of smile. A favorable aesthetic effect can be achieved with a good knowledge of application sites and individually selected doses. When determining the dose, which is described in the literature between 2 IU and 10 IU onabotulin per page, researchers take into account not only the type of corrected smile, the number of puncture points, but also gender and age of the patient.
Keywords: gummy smile; botulinum toxin; aesthetic medicine